KAJIAN ESTETIKA PADA FASAD MASJID AGUNG KOTA SUKABUMI (Studi Kasus :Masjid agung kota sukabumi) - Ayu Oktaviani; Oktaviandi, Wildan Rizqi (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2022)
The mosque building is one of the worship buildings for religious facilities for adherents of Islam which is used as a place to worship. According to Prijotomo in the History of Architecture (2009) buildings that have aesthetic value or can be said to be beautiful buildings. In this study, the method used is a qualitative descriptive method. the author who became the instrument in the research and the analysis was carried out continuously from the beginning of the study to data analysis. From this research it can be concluded that the Great Mosque of Sukabumi City applies formation elements on the facade including the entrance gate, Ground floor zone, windows and entrances, guardrails, roofs and ornaments on the building and has aesthetic values of the facade by considering the layout. location, geometry, proportion, symmetry, rhythm (rhythm) and scale so as to produce a facade that has a 'feel'.